Qualitative Analysis of Borax with Butterfly Pea Flower Extract (clitoria ternatea) in Tofu Sold by Traders - RIRI SAFITRI (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2026)
Butterfly pea flower extract can function as a qualitative indicator in detecting borax in various foods, which is characterized by a color change from blue to green or other colors after interacting with samples containing borax. Borax is often used as a food preservative, for example in tofu. The impact of the use of borax added to food can have a negative impact on the health of people who consume it. This study aims to describe the borax content in tofu sold by traders in the Pasar 6 Kualanamu village area, Beringin District. This study is a qualitative study with a descriptive approach. This approach is used because the study focuses on observing phenomena that occur visually, namely the color change of butterfly pea flower extract (Clitoria ternatea) when reacting with tofu samples to determine the presence or absence of borax in the food ingredients being tested. The results of the qualitative analysis of borax with butterfly pea flower extract (Clitoria ternatea) on all tofu samples are negative with the resulting color blue. Interpretation of the color results after adding butterfly pea flower extract, if the result is blue or purple indicates negative borax (does not contain borax), if the result is bluish green indicates positive borax (contains borax). This shows that the tofu obtained from traders A, B, C who sell in the village area of ​​​​Kualanamu Market 6 does not contain borax. Awareness of the dangers of using borax is very necessary for all parties to avoid the negative impacts caused by the use of borax in food.